2019
DOI: 10.3390/agriculture9010011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wilting Intensity, Dry Matter Content and Sugar Addition on Nitrogen Fractions in Lucerne Silages

Abstract: Pre-ensiling treatments can significantly influence the composition of lucerne (Medicago sativa L.) silages (LS). Besides dry matter (DM) content and availability of water-soluble carbohydrates (WSC), wilting intensity may exert a strong impact on the crude protein (CP; nitrogen [N] × 6.25) fractions. The present study aimed to evaluate the effects of DM level, wilting intensity, and sucrose addition on N compounds and fermentation products in LS. Pure lucerne stand (cultivar Plato) was wilted with either high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
1
16
1
Order By: Relevance
“…In all growth stages, the addition of the scotta decreased the pH, which reached 5.27 in MB and 4.32 in EF and LF. The latter values were lower than those achieved by adding alfalfa forage with fresh whey (pH 4.67) [32], sucrose (4.58) [33], formic acid (4.36) [34], a chemical additive consisting of formic acid, propionic acid, formate ammonium, and benzoic acid (4.38), a bacterial inoculum (homofermentative and heterofermentative lactic bacteria) (4.47) [15], or a previously fermented alfalfa juice (4.53) [13].…”
Section: Discussionmentioning
confidence: 62%
“…In all growth stages, the addition of the scotta decreased the pH, which reached 5.27 in MB and 4.32 in EF and LF. The latter values were lower than those achieved by adding alfalfa forage with fresh whey (pH 4.67) [32], sucrose (4.58) [33], formic acid (4.36) [34], a chemical additive consisting of formic acid, propionic acid, formate ammonium, and benzoic acid (4.38), a bacterial inoculum (homofermentative and heterofermentative lactic bacteria) (4.47) [15], or a previously fermented alfalfa juice (4.53) [13].…”
Section: Discussionmentioning
confidence: 62%
“…On the other hand, immediately after the fermentation of the raw material, a variation in pH occurs, which reaches values between 5.5 and 6 due to the low concentration of lactic, acetic and propionic acid in the medium (Kung et al 2018). After 96 hours of fermentation in the silage there is a good production of lactic acid product of the action of lactic bacteria (Muck 2013), reducing the pH to values lower than 4.5, a pH lower than these values allows to obtain an optimal silage product nutritional, microbiological and organoleptic quality, without danger of transmitting diseases for animals (Wang et al 2016;Hartinger et al 2019;Tyrolová et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…An in vitro study was previously performed where eight varyingly pre-treated AS differing in terms of crude protein composition and silage fermentation quality (Hartinger et al, 2019a) were incubated in an in vitro Rusitec system (Hartinger et al, 2019b). The preparation and chemical composition of the eight AS have been described in detail and can be obtained from Hartinger et al (2019a). Briefly, pure alfalfa sward was harvested and similarly spread on either black plastic in the sun, i.e., high-intensity wilting treatment (HI), or on white plastic in the shade, i.e., low-intensity wilting treatment (LI).…”
Section: Methodsmentioning
confidence: 99%
“…Excessive ruminal ammonia production results in its absorption by the host, before it is excreted as urea into the environment (Coblentz and Grabber, 2013). In order to improve the ruminal fermentation and N retention, the effects of different alfalfa pre-ensiling treatments, i.e., dry matter (DM) concentration, wilting intensity and sucrose addition on the resulting AS crude protein fractions was investigated using eight different AS (Hartinger et al, 2019a). It was observed that wilting alfalfa with high intensity to 35% DM concentration in combination with sucrose addition at ensiling lead to highest true protein preservation, as well as a generally improved silage quality.…”
Section: Introductionmentioning
confidence: 99%